2015
DOI: 10.21273/horttech.25.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Partitioning of Nutrients in Blackberry and Raspberry and Evaluating Plant Nutrient Status for Accurate Assessment of Fertilizer Requirements

Abstract: Raspberry and blackberry (Rubus sp.) plantings have a relatively low nutrient requirement compared with many other perennial fruit crops. Knowledge of annual accumulation of nutrients and periods of rapid uptake allows for better management of fertilization programs. Annual total nitrogen (N) accumulation in the aboveground plant ranged from 62 to 110 and 33 to 39 lb/acre in field-grown red raspberry (Rubus idaeus) and blackberry (Rubus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
1
27
0
1
Order By: Relevance
“…Grape displays the same range of NH 4 + concentrations as other fleshy fruits such as red fleshy fruits, e.g. Strawberry (Taghavi et al, 2004), Blackberry or Raspberry (Strik and Bryla, 2015).…”
Section: Ammoniummentioning
confidence: 99%
“…Grape displays the same range of NH 4 + concentrations as other fleshy fruits such as red fleshy fruits, e.g. Strawberry (Taghavi et al, 2004), Blackberry or Raspberry (Strik and Bryla, 2015).…”
Section: Ammoniummentioning
confidence: 99%
“…Primocane leaf nutrient analysis is an important tool used by growers to develop and modify nutrient management programs. The nutrient concentrations of primocane leaves sampled in late July to early August are compared with published standards (Hart et al, 2006) with the goal of improving the nutrient status of the subsequent floricanes (the following year) through fertilization in autumn or spring (Strik and Bryla, 2015). In our study, primocane leaf concentrations of N, K, Ca, Mg, and B were low or below the recommended sufficiency ranges in one or both years, similar to what Harkins et al (2014) found during the establishment years, although in their case, K was sufficient in the planting.…”
Section: Augmentioning
confidence: 99%
“…Nutrient uptake varies among crops, between growing seasons, and between production sites (Chang et al, 2012;Pradubsuk and Davenport, 2010;Ristvey et al, 2007;Scagel et al, 2007). The nutrient requirement of a given species or cultivar also fluctuates within a growing season (Strik and Bryla, 2015), which is difficult to predict and has rarely been reported.…”
mentioning
confidence: 99%